Penerapan Murottal Al-Qur’an Surah Ar-Rahman Ustaz Hanan Attaki Terhadap Tingkat Stres Mahasiswa Universitas ‘Aisyiyah Surakarta - Nurul Nuha Tasliyah; Irma Mustika Sari (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Background: High levels of stress can result in biological, psychological and social problems and even serious harm to a person. Emotional prevalence in Central Java is characterized by 95,461 depressive symptoms. Stress in students can originate from activities and also academic assignments. Objective: Therapy that can be carried out by Muslims with an Islamic approach, namely psychoreligious by listening to the holy verses of the Koran or murottal Al-Qur'an. This research aims to determine the effect of providing murottal Al-Qur'an on stress levels in students at 'Aisyiyah University, Surakarta. The research respondents were students at 'Aisyiyah University, Surakarta, female, aged 18-22 years, from the faculty of health sciences and not deaf. Methods: This study measured the stress level of the pretest and posttest design. The subjects of this study amounted to 2 respondents. The questionnaire used in this study was the DASS (Depression Anxiety Stress Scale) questionnaire to measure student stress levels. Results: Before being given murottal Al-Qur'an the level of stress was high, and after being given murottal Al-Qur'an the level of stress was mild. Conclusion: The results show that there is a significant reduction in stress levels in 'Aisyiyah Surakarta University students, after being given Al-Qur'an murottals.